Espaços claustrofóbicos na obra de Lourenço Mutarelli - Pascoal Farinaccio (Estudos de Literatura Brasileira Contemporânea)
This paper proposes the existence of relations between psychological states of depression and claustrophobic spaces in the literary work of Lourenço Mutarelli; in this perspective, it analyses passages from the novels by the author to indicate the thematization and recurrence of these suggested relations and its possible meanings.